FMOD Alleviates Depression-Like Behaviors by Targeting the PI3K/AKT/mTOR Signaling After Traumatic Brain Injury - Xuekang Huang; Ziyu Zhu; Mengran Du; Chenrui Wu; Jiayuanyuan Fu; Jie Zhang; Weilin Tan; Biying Wu; Lian Liu; Z. B. Liao (NeuroMolecular Medicine, 2024)
Depression frequently occurs following traumatic brain injury (TBI). However, the role of Fibromodulin (FMOD) in TBI-related depression is not yet clear. Previous studies have suggested FMOD as a potential key factor in TBI, yet its association with depression post-TBI and underlying mechanisms are not well understood. Serum levels of FMOD were measured in patients with traumatic brain injury using qPCR. The severity of depression was assessed using the self-depression scale (SDS). Neurological function, depressive state, and cognitive function in mice were assessed using the modified Neurological Severity Score (mNSS), forced swimming test (FST), tail suspension test (TST), Sucrose Preference Test (SPT), and morris water maze (MWM). The morphological features of mouse hippocampal synapses and neuronal dendritic spines were revealed through immunofluorescence, transmission electron microscopy, and Golgi-Cox staining. The protein expression levels of FMOD, MAP2, SYP, and PSD95, as well as the phosphorylation levels of the PI3K/AKT/mTOR signaling pathway, were detected through Western blotting. FMOD levels were decreased in TBI patients’ serum. Overexpression of FMOD preserved neuronal function and alleviated depression-like behaviour, increased synaptic protein expression, and induced ultrastructural changes in hippocampal neurons. The increased phosphorylation of PI3K, AKT, and mTOR suggested the involvement of the PI3K/AKT/mTOR signaling pathway in FMOD’s protective effects. FMOD exhibits potential as a therapeutic target for depression related to TBI, with its protective effects potentially mediated through the PI3K/AKT/mTOR signaling pathway.